2020
DOI: 10.1186/s12913-020-05578-8
|View full text |Cite|
|
Sign up to set email alerts
|

A pain relieving reimbursement program? Effects of a value-based reimbursement program on patient reported outcome measures

Abstract: Background Value-based reimbursement programs have become increasingly common. However, little is known about the effect of such programs on patient reported outcomes. Thus, the aim of this study was to analyze the effect of introducing a value-based reimbursement program on patient reported outcome measures and to explore whether a selection bias towards less complicated patients occurred. Methods This is a retrospective observation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…In their study on a similar competition-inducing reform with a bundle payment arrangement introduced in Stockholm, but for elective spine surgery, Eriksson and colleagues [ 15 ] also found no effects on PROMs. As they discuss in their paper, one reason for the lack of effect relates to the incentive structure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In their study on a similar competition-inducing reform with a bundle payment arrangement introduced in Stockholm, but for elective spine surgery, Eriksson and colleagues [ 15 ] also found no effects on PROMs. As they discuss in their paper, one reason for the lack of effect relates to the incentive structure.…”
Section: Discussionmentioning
confidence: 99%
“…As they discuss in their paper, one reason for the lack of effect relates to the incentive structure. Within the spine surgery program, providers were given stronger financial incentives to avoid negative outcomes than to reach positive outcomes [ 15 ]. This is also the case for the reform being analyzed in the present paper.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The combination of a value-oriented payment system with a comprehensive definition of value can stimulate cross-healthcare collaboration. By making healthcare actors financially responsible for delivering the outcomes that matter, providing efficient pathways to deliver this value is incentivized [ 30 ]. The careful integration of outcome, process, and structure indicators can be used to direct and safeguard VBHC implementation to make sure the focus on delivering value is not lost in translation.…”
Section: Discussionmentioning
confidence: 99%
“…Following publication of the original article [ 1 ], the authors identified some errors in Table 6 . The correct table and caption have been included in this correction, and the original article has been corrected.…”
mentioning
confidence: 99%